"Think locally, Act globally" : 適正技術再訪 - 小林, 信一 (研究 技術 計画, 2013)
The environmental problems and oil crisis, which attracted public attention in the 1970s, undermined optimism about progress in technology and economy. In response to this trend, the "appropriate technology" was proposed as a way of creating technologies that fit to the diverse natural, social and historical conditions involved in problems to be addressed. While this concept has not been fully successful because of the complexity of those conditions, the advance in information and communication technology has changed the situation by making a huge number of combinatorial calculations feasible. It is now easier to take into account the individuality, interdependence and history of the entities involved in a problem, thus reviving the idea of appropriate technology. The "smart grid" is an exemplary result of this approach. It is expected that reevaluation of the appropriate technology makes it possible to solve local problems by applying knowledge from all over the world.